Comorbidity of self-harm and disordered eating in young people: evidence from a UK population-based cohort. (June 2021) - Bould, Helen; Warne, Naomi; Heron, Jon; Mars, Becky; Moran, Paul; Stewart, Anne; Munafo, Marcus; Biddle, Lucy; Skinner, Andy; Gunnell, David
Abstract : Aims: Self-harm and eating disorders are often comorbid in clinical samples but their co-occurrence in the general population is unclear. Given that only a small proportion of individuals who self-harm or have disordered eating present to clinical services, and that both self-harm and eating disorders are associated with substantial morbidity and mortality, we aimed to study these behaviours at a population level. Method: We assessed the co-occurrence of self-harm and disordered eating behaviours in 3384 females and 2326 males from a UK population-based cohort: the Avon Longitudinal Study of Parents and Children (ALSPAC). Participants reported on their self-harm and disordered eating behaviours (fasting, purging, binge-eating and excessive exercise) in the last year via questionnaire at 16 and 24 years. At each age we assessed how many individuals who self-harm also reported disordered eating, and how many individuals with disordered eating also reported self-harm. Result: We found high comorbidity of self-harm and disordered eating. Almost two-thirds of 16-year-old females, and two-in-five 24-year-old males who self-harmed also reported some form of disordered eating. Young people with disordered eating reported higher levels of self-harm at both ages compared to those without disordered eating. Conclusion: As self-harm and disordered eating commonly co-occur in young people in the general population, it is important to screen for both sets of difficulties to provide appropriate treatment.